Possible nitrogen fertilization of the early Earth Ocean by microbial continental ecosystems - Thomazo, Christophe (Nat Commun, 2018)
While significant efforts have been invested in reconstructing the early evolution of the Earth’s atmosphere–ocean–biosphere biogeochemical nitrogen cycle, the potential role of an early continental contribution by a terrestrial, microbial phototrophic biosphere has been largely overlooked. By transposing to the Archean nitrogen fluxes of modern topsoil communities known as biological soil crusts (terrestrial analogs of microbial mats), whose ancestors might have existed as far back as 3.2 Ga ago, we show that they could have impacted the evolution of the nitrogen cycle early on. We calculate that the net output of inorganic nitrogen reaching the Precambrian hydrogeological system could have been of the same order of magnitude as that of modern continents for a range of inhabited area as small as a few percent of that of present day continents. This contradicts the assumption that before the Great Oxidation Event, marine and continental biogeochemical nitrogen cycles were disconnected.